Efektivitas Penerimaan Pajak Restoran Dalam Meningkatkan Pendapatan Asli Daerah (PAD) Pada Badan Pengelolaan Keuangan, Pendapatan dan Aset Daerah (BPKPAD) Kota Cilegon - Refi Pratiwi; Iis Ismawati; Destia Maulid; Mas Iman Kusnandar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This writing aims to find out restaurant tax revenue in increasing Regional Original Revenue at the Cilegon City Regional Financial, Revenue and Asset Management Agency. The rapidly growing number of restaurants in Cilegon City will get optimal results in restaurant tax revenue and become a source of regional income. This writing uses descriptive methods with data collection techniques in the form of interviews, observations, documentation and literature studies. The object of writing is the office of the Cilegon City Regional Financial, Revenue and Asset Management Agency on the staff of the Regional Tax and PAD Control Division. The results of the writing show that the effectiveness of restaurant tax revenue fluctuates every year with realization exceeding the target. Restaurant tax in increasing local revenue is still in the small category. The Cilegon City Regional Finance, Revenue and Asset Management Agency experiences obstacles to restaurant tax revenue, namely the lack of understanding of taxation by the community, but there are several efforts made such as collecting data on potential new taxpayers, having Tapping Boxes and PDT, controlling and checking taxes, reward activities, conducting socialization and education.